Big Red - Kjelgaard, Jim, 1910-1959.; Kuhn, Bob (New York : Holiday House, 1973)
A trapper's son and a champion Irish Setter roam wilderness areas and grow to maturity together.
Elem. School Library Collection.
School Library Journal starred.
School Library Journal.
5.4.
5.4
5-8
Keywords: Dogs -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Trappers -- Juvenile fiction; Dogs -- Fiction; Fathers and sons -- Fiction; Trappers -- Fiction; Dogs -- Fiction; Father-son relationship -- Fiction; Trappers -- Fiction